PRESENTASI DIRI FASHION ICON HIJAB SYAR’I KOTA PEKANBARU MELALUI MEDIA SOSIAL INSTAGRAM - Aidil Emmil Adliandri; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Nowadays, trend fashion has been reach the Muslim dress that in recent years was ogled by some Indonesian designer. So now appear some trends, one of them is hijab syar’i. If looking at the phenomenon in social media instagram that show the existence of the people who wear hijab syar’i, it causes the appearence of the term fashion icon hijab syar’i. The activities such as review look, endorser, life style trensetter, and dakwah wass also done by fashion icon hijab syar’i in Pekanbaru. The aim of this research is to know their motive in wearing hijab syar’i, front stage life, and back stage life of fashion icon hijab syar’i.This research used qualitative method and using phenomenology approach. There are three informant fashion icon hijab syar’i in this research from Pekanbaru that was chosen purposively. The data was collected through observation, deep interview, and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The result of this research shows that the motive of fashion icon hijab syar’i in wearing hijab syar’i, is past motive such as fashionable motive, psikological motive, and theological motive. While the motive of hope is to deepen their religious knowledge and inspire others. Their activity in the front stage is OOTD or Outfit of the Day, endorse, life style, and dakwah. The manner or style that they want to build is polite and elegant woman and relaxed Muslimah. Meanwhile the attribute of their appearance is veil (Khimar), dress (Gamis), manset, socks, shoes, accessories, and bag. The activities in the back stage are household activity, gathering with other fashion icon hijab syar’i, business and pengajian. The attribute of their appearance are khimar that is wore simply or sliding khimar and syar’i dress that is wore depend on the situation of mukhrim. Besides that, this research categorize three kinds of fashion icon hijab syar’i in Pekanbaru, they are modist fashion icon hijab syar’i, simple fashion icon hijab syar’i, and totaliter fashion icon hijab syar’i.Keyword: self presentation, trend fashion, hijab syar’i, motive, social media, back stage, front stage